The analysis of entrepreneurial smallholder farmers: Evidence from Thailand - Jiumpanyarach, Waripas (Asian Journal of Agriculture and Rural Development, 2025)
The success and sustainability of smallholder agricultural entrepreneurship in Thailand were investigated by regional disparities. Data were collected from 302 smallholder farmers through questionnaires, with regional sample sizes of 67 (North), 64 (South), 60 (East), 51 (Central), and 60 (Northeast). The data were subsequently analyzed using a logit regression model. The findings of this study revealed that 46% of respondents achieved entrepreneurial success, defined as a monthly profit exceeding 17,000 THB (570 USD). This success was primarily in the Eastern and Southern regions. Agricultural types, infrastructure, and market profitability were identified as significant positive drivers of entrepreneurial success. Conversely, the Northern and Northeastern regions exhibited the highest rates of entrepreneurial failure. This was associated with limited financial access, inadequate community management, and restricted development of value-added products. These factors, compounded by a lack of formal loan support, resulted in significant income constraints. Furthermore, post-harvesting and logistical challenges, alongside individual and community mindsets, were found to significantly influence business outcomes across all regions. The success approach integrates targeted government and private sector support to improve infrastructure, expand financial accessibility through customized loan programs, and enhance market profitability via optimized value chains, thereby fostering sustainable growth and improved livelihoods.